Forms of On-Line and On-Site Employment - Agnieszka Ziomek; Katarzyna ŁASIŃSKA; Andrzej PIECZYŃSKI; Janusz SZAJNA (Communications of International Proceedings, 2023)
The emergence of various forms of work in the contemporary labour market has prompted social dialogues on their terms and conditions. The aim of this paper is to present the characteristics of nine new forms of on-line and on-site work in the context of working conditions in different professions and to point out the effects they have on the worker and the economy. To define the concept of new forms, a proposal contained in the Eurofound document "Gig economy report: employment status" (2019) was adopted. The new forms significantly exceed the insofar employment standards with regard to place, time as well as remuneration formats. Even though they make it possible to acquire new contacts and experience as well as increase income, their new levels of flexibility also result in instability, greater volatility, irregularity and discontinuity.